2006
DOI: 10.1111/j.1742-4658.2006.05130.x
|View full text |Cite
|
Sign up to set email alerts
|

The catalysis of the SARS 3C‐like protease is under extensive regulation by its extra domain

Abstract: The 3C‐like protease of the severe acute respiratory syndrome (SARS) coronavirus has a C‐terminal extra domain in addition to the chymotrypsin‐fold adopted by piconavirus 3C proteases hosting the complete catalytic machinery. Previously we identified the extra domain to be involved in enzyme dimerization which has been considered essential for the catalytic activity. In an initial attempt to map out the extra‐domain residues critical for dimerization, we have systematically generated 15 point mutations, five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
229
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(238 citation statements)
references
References 43 publications
7
229
0
2
Order By: Relevance
“…Besides the N-terminal finger, it has been reported that domain III also contributes well to dimerization of SARS-CoV 3CL pro (6,14). In agreement with this result, domain III undergoes a dramatic conformational switch relative to the chymotrypsin fold (domain I and II) in G11A monomer, rotating by 24°comparing with its normal position in wild-type dimer.…”
Section: Dimerization-related Structures (The N-terminal Finger and Dsupporting
confidence: 63%
See 3 more Smart Citations
“…Besides the N-terminal finger, it has been reported that domain III also contributes well to dimerization of SARS-CoV 3CL pro (6,14). In agreement with this result, domain III undergoes a dramatic conformational switch relative to the chymotrypsin fold (domain I and II) in G11A monomer, rotating by 24°comparing with its normal position in wild-type dimer.…”
Section: Dimerization-related Structures (The N-terminal Finger and Dsupporting
confidence: 63%
“…Why Does Mutation of Gly-11 Cause the Complete Dissociation of the Dimer in Crystal?-To date, the N-terminal finger (residues 1-7) and domain III have been identified to extensively mediate monomer-monomer interactions of SARS-CoV 3CL pro (6,10,14,15,18). Now we have brought forward a new structural element that is also vital for dimerization of the protease, namely ␣-helix AЈ (residues 10 -15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each subunit contains a catalytic dyad defined by His41 and Cys145 in the active site (Fig. However, the enzyme is catalytically compe-tent only after dimer formation [9][10][11][12][13][14][15][16][17][18][19][20]. However, the enzyme is catalytically compe-tent only after dimer formation [9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%